If it's not what You are looking for type in the equation solver your own equation and let us solve it.
2x-3+4(3x-12)-2(4x-9)=x+4
We move all terms to the left:
2x-3+4(3x-12)-2(4x-9)-(x+4)=0
We multiply parentheses
2x+12x-8x-(x+4)-48+18-3=0
We get rid of parentheses
2x+12x-8x-x-4-48+18-3=0
We add all the numbers together, and all the variables
5x-37=0
We move all terms containing x to the left, all other terms to the right
5x=37
x=37/5
x=7+2/5
| -24=12(-x-8) | | (15x+4)/4=11 | | x÷2=5/6 | | 3(2x–4)=2(x+14) | | 8(2d-3)=3(4d-3) | | 2(5x+2)=4(2x+2) | | 2r-5/3=r+1/2 | | 4y-21=24 | | 3j/4+2=8 | | 8k-14=3k+16 | | 5y-8=3y-3 | | 4(x+3)=7x+3-3x | | -9+10(j+11)=-7 | | -3x+6=8x-3x | | 4(x+3)=7x+3-3x= | | 4(2p+1)=34-2p | | -5w+9w=16-48 | | 1-x/6+2x/3-1-7x/4=13/6 | | X=15-n/2 | | -15x+21=-19-5x | | 2(c+14)=8 | | 2w–13=–9 | | 8x/3=5x/2 | | –2(y–10)=–12 | | t/13+10=6 | | t–13+10=6 | | t/–13+10=6 | | 6+9n= | | 10n+4= | | c/11+5=5 | | 4x−7−6x=29 | | 9(p+2)=18 |